Information Technology Improves Emergency Department Patient Discharge Instructions Completeness and Performance on a National Quality Measure - Bell, E.J.; Takhar, S.S.; Beloff, J.R.; Schuur, J.D.; Landman, A.B. (Applied Clinical Informatics, 2013)
Objectives: To compare the completeness of Emergency Department (ED) discharge instructions before and after introduction of an electronic discharge instructions module by scoring compliance with the Centers for Medicare and Medicaid Services (CMS) Outpatient Measure 19 (OP-19).Methods: We performed a quasi-experimental study examining the impact of an electronic discharge instructions module in an academic ED. Three hundred patients discharged home from the ED were randomly selected from two time intervals: 150 patients three months before and 150 patients three to five months after implementation of the new electronic module. The discharge instructions for each patient were reviewed, and compliance for each individual OP-19 element as well as overall OP-19 compliance was scored per CMS specifications. Compliance rates as well as risk ratios (RR) and risk differences (RD) with 95% confidence intervals (CI) comparing the overall OP-19 scores and individual OP-19 element scores of the electronic and paper-based discharge instructions were calculated.Results: The electronic discharge instructions had 97.3% (146/150) overall OP-19 compliance, while the paper-based discharge instructions had overall compliance of 46.7% (70/150). Electronic discharge instructions were twice as likely to achieve overall OP-19 compliance compared to the paper-based format (RR: 2.09, 95% CI: 1.75 – 2.48). The largest improvement was in documentation of major procedures and tests performed: only 60% of the paper-based discharge instructions satisfied this criterion, compared to 100% of the electronic discharge instructions (RD: 40.0%, 95% CI: 32.2% – 47.8%). There was a modest difference in medication documentation with 92.7% for paper-based and 100% for electronic formats (RD: 7.3%, 95% CI: 3.2% – 11.5%). There were no statistically significant differences in documentation of patient care instructions and diagnosis between paper-based and electronic formats.Conclusions: With careful design, information technology can improve the completeness of ED patient discharge instructions and performance on the OP-19 quality measure.Citation: Bell EJ, Takhar SS, Beloff JR, Schuur JD, Landman AB. Information technology improves emergency department patient discharge instructions completeness and performance on a national quality measure: A quasi-experimental study. Appl Clin Inf 2013; 4: 499–514 http://dx.doi.org/10.4338/ACI-07-RA-0046
Keywords: Computerized medical records systems; emergency care information systems; patient discharge; quality improvement; health care reform